Fungsi Musik Dayak Kanayatn - Amir Razak; Ferdinand Ferdinand (Institut Seni Indonesia Yogyakarta, 2019)
Kanayatn Dayak music in the anthro-social aspect experienced a multiplication of functions caused by sublimation of local musical genius intra-extras and the human needs of the community, where until now the description of ethnic music, especially Dayak Kanayatn is still not widely explained in the cultural context, so this research focuses on describing functions of Dayak kanayatn music in community activities.Qualitative narrative is an effort to describe the process or function of Dayak Kanayatn music so that it can provide interpretation in accordance with facts in the community, where data collection is through literature study, observation and documentation while data analysis uses domain interpretation techniques.The results showed that Dayak Kanayatn music had several functions including; entertainment facilities, commodification of tourism, ratification of social institutions, integration of social groups, propaganda media, local cultural identity, informal education facilities.